Mentransformasikan Keuangan Syariah Menuju Pertumbuhan Ekonomi Yang Tangguh Dan Berkelanjutan - Tohirin Tohirin; Meita Larasati (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This community activity program is aimed at CLSU Philippines students, so that they will have an understanding of the principles of Islamic finance. Students were chosen because it is hoped that in the future they will be able to become pillars in the transformation of Islamic financial principles to the wider community. This activity was carried out directly at the Central Luzon State University Campus. The team conducted the activity from July 4 to 7, 2023. This activity went well, because it received positive support from the stakeholders involved, besides that the students involved also had high enthusiasm for the implementation of the program that we did.